Sustainable technology-enabled innovations for ageing-in-place: The Singapore example - TAN, Hwee-pink (Institutional Knowledge at Singapore Management University, 2019)
The increasing ageing population worldwide exacerbates problems associated with shrinking manpower, shortage in institutionalized resources and healthcare/eldercare facilities, as well as lack of professionals who are trained in geriatric care. Ageing-in-place allows seniors to continue staying in the familiarity of their residential homes, and leverage support from the community for day-to-day needs, while maintaining independence and privacy. This is especially important for vulnerable seniors who live alone as well as those who require barrier-free access. Emerging technologies can play an essential role in facilitating such an ageing-in-place model, through ambient monitoring and intelligence, coupled with cross-disciplinary sense-making through artificial intelligence approaches. The sustainability of such technological innovations requires collaborations and integrative efforts at the stakeholder, technology and sense-making fronts. In this chapter, the authors provide a review of existing technology-enabled ageing-in-place initiatives, and describe a collaborative framework to enhance the sustainability of these efforts. They then share their experiences gleaned through various collaborative efforts that combine technology with socio-behavioral sciences and clinical validation, backed by a collaborative ecosystem of key stakeholders, for vulnerable seniors to age well and gracefully in their own homes and local community. Finally, the authors outline a cross-disciplinary and collaborative research agenda necessary to ensure sustainability of similar initiatives.